IMPROVISATION IN THE TEACHING OF INFORMATION TECHNOLOGY IN RURAL COMMUNITIES SECONDARY SCHOOL IN AHOADA, LGA, RIVER STATE, NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
ICT is an essential part of the education system in Nigeria. However, it is perceived among learners as a tedious and challenging subject. The primary objective of the current study was to enhance the teaching and learning of mathematics using improvisation. The study also examined the role of student's location on ICT learning when the learning material is improvised. The population of the study included secondary school students in both rural and urban areas of Ahoada, Lga, River State, Nigeria. A total of 68 secondary school students constituted the study samples. A quasi-experimental design was used. Two hypotheses were tested, and it was concluded that improvisation of learning material enhances student's performance in ICT. Also, the study found that student's location does not affect performance in ICT when instructional material is improvised. The findings and recommendations are discussed.